2010
DOI: 10.1080/13594320903024922
|View full text |Cite
|
Sign up to set email alerts
|

Critique and review of leader–member exchange theory: Issues of agreement, consensus, and excellence

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 67 publications
7
109
0
1
Order By: Relevance
“…Under minimal job autonomy conditions, LMX is unrelated to creative work involvement. This implies that a high-quality LMX relationship, which is associated with many numerous work and non-work outcomes (Gerstner & Day, 1997;Ilies et al, 2007;Schyns & Day, 2010), is not sufficient when employees experience job design constraints. Our findings point to the importance of considering both the leader-member relationship and job design issues for increasing creative work involvement.…”
Section: Discussionmentioning
confidence: 98%
“…Under minimal job autonomy conditions, LMX is unrelated to creative work involvement. This implies that a high-quality LMX relationship, which is associated with many numerous work and non-work outcomes (Gerstner & Day, 1997;Ilies et al, 2007;Schyns & Day, 2010), is not sufficient when employees experience job design constraints. Our findings point to the importance of considering both the leader-member relationship and job design issues for increasing creative work involvement.…”
Section: Discussionmentioning
confidence: 98%
“…Maintaining such relationships are noteworthy as research has found that fostering positive relationships can have impacts over time on critical organizational outcomes such as performance, job satisfaction and citizenship behaviors (Schyns and Day, 2010). Moreover, the workplace is becoming more dependent on teams and collaboration (Kozlowski and Bell, 2003), and informal feedback may continually come from our peers owing to increases in the use of processes such as self-managed work groups where leadership functions, such as feedback provision, are shared.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses have found higher correlations between leader-rated LMX with performance than with follower-rated LMX (e.g., Gerstner & Day (1997). These differences might be conceptual or methodological in nature (see Schyns & Day, 2010). It would seem therefore important to test whether there are differences between leader-and follower-rated effects on task, citizenship, and counterproductive performance, and whether these effects hold even when common source or method bias is controlled for.…”
Section: Moderators Of the Lmx And Performance Relationshipmentioning
confidence: 99%